(untitled) (Tanzania Medical Journal, 2020)
Introduction Gout is one of inflammatory disorders of the joints, which is common in elderly men and mostly affecting the tarso – phalangeal joint of the big toe. Despite its increase in prevalence and associated morbidity and mortality for the past few decades, there is limited knowledge regarding this disease in the general population. Objective To assess knowledge and attitudes towards gout among adult community members in Temeke district. Methodology A descriptive cross – sectional study was conducted at household level among 323 conveniently selected adult community members in Temeke district from 8th - 15th September, 2017 to determine their knowledge and attitudes towards gout using self-administered questionnaires. Results Among the 323 participants, 67.8% were females, with mean age of 35.33 years and most (55.4%) had primary education. Those who knew or had knowledge on etiology, risk factors, complications and preventive measures were respectively 3.7%, 18.7%, 12% and 9.9% on average. Furthermore, approximately 79.1% were undecided with regards to different aspects of gout. Conclusion The knowledge towards gout in this studied population is low and majority have undecided/neutral attitude towards several aspects of gout. Education provision in addition to emphasis on attitudes change is vital to address this problem. Keywords: Gout, Risk Factors, Knowledge and Attitudes.